what is the simplified expression
![what is the simplified expression class=](https://us-static.z-dn.net/files/de3/420e4dfb44a82384e170230709f91f67.jpg)
Solution:
[tex]\rightarrow \frac{4^{-3} \times 3^{4} \times 4^{2} }{3^{5} \times 4^{-2} }[/tex]
[tex]\rightarrow 4^{-3 + 2} \times 3^{4 - 5} \times 4^{2} }[/tex]
[tex]\rightarrow 4^{-1} \times 3^{-1} \times 16}[/tex]
[tex]\rightarrow \frac{1}{4} \times \frac{1}{3} \times 16}[/tex]
[tex]\rightarrow \frac{1}{12} \times 16}[/tex]
[tex]\rightarrow \frac{16}{12}[/tex]
[tex]\rightarrow \boxed{\bold{\frac{4}{3} \tex\text{ (Option B)}}}[/tex]
Answer:
[tex]\dfrac43[/tex]
Step-by-step explanation:
[tex]\dfrac{4^{-3}\cdot3^4\cdot4^2}{3^5\cdot4^{-2}}[/tex]
Separate like terms:
[tex]\implies \dfrac{4^{-3}\cdot4^2}{4^{-2}}\cdot \dfrac{3^4}{3^5}[/tex]
Use exponent rule [tex]a^b \cdot a^c=a^{(b+c)}[/tex] :
[tex]\implies \dfrac{4^{(-3+2)}}{4^{-2}}\cdot \dfrac{3^4}{3^5}[/tex]
[tex]\implies \dfrac{4^{-1}}{4^{-2}}\cdot \dfrac{3^4}{3^5}[/tex]
Use exponent rule [tex]\dfrac{a^b}{a^c}=a^{(b-c)}[/tex]
[tex]\implies 4^{(-1--2)}\cdot {3^{(4-5)}[/tex]
[tex]\implies 4^{1}\cdot {3^{-1}[/tex]
Use exponent rule [tex]a^{-1}=\dfrac{1}{a}[/tex]
[tex]\implies 4\cdot \dfrac13[/tex]
[tex]\implies \dfrac43[/tex]